Optimalisasi Kemitraan Masyarakat untuk Pengembangan Kapasitas dan Mutu Produksi Kue Bolen Pisang Raja 'Nona Perry' dengan Pendekatan Ekonomi Hijau di Surabaya - Sujani Sujani; Rena Febrita Sarie; Muharom Muharom (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The PKM partner is Mrs. Popy Dwi Novitasari and Mrs. Feri Retno Nurhayati. The owner of the "Nona Perry" banana bolen cake business takes the name from both of them. The business is located at Lempung Baru Street No. 1, Lontar, Sambikerep Subdistrict, Surabaya, East Java, 60185. The priorities of the issues are as follows: 1) There is no proper management of the storage of banana ingredients for production, 2) Inconsistency in production as it is still limited to orders, 3) There is no product diversification, "Nona Perry" Bolen Cake only has 2 flavor variations, which are chocolate and cheese, 4) There is no branding, although there is already a brand "Nona Perry" for the bolen product, the strengthening of the brand image "Nona Perry" still needs to be improved. 5) The market segment is still limited to orders from colleagues and peers, 6) There is no massive promotion, only limited to WhatsApp and Instagram groups. 7) The partner has minimal knowledge of working capital and profit-loss calculations, 8) The workforce is unstable, 9) Partners still have limited knowledge about production waste processing and green economy, 10) Partners still have limited knowledge to innovate on advanced production processing methods implemented through the development of appropriate technology (TTG), training, mentoring, and partnerships. The results of implementing activities in this program include coordination of program implementation with partners, dissemination of TTG, procurement of equipment, and training for healthy production, training and mentoring for online and offline sales, training and mentoring for label and logo creation, training and mentoring for financial transaction recordkeeping of businesses. The impact of this activity is an increase in the capacity and quality of partner products by 30%, an increase in partner turnover by 30%, and an increase in partners' knowledge and skills by 50%.